Toxicity profile of double-agent adjuvant chemotherapy after concurrent chemoradiation and brachytherapy in locally advanced cervical cancer: Comparison with standard chemoradiation protocol - Tejas Pandya; Virender Suhag; Subhash Ranjan; B S Sunita; Sujata Pandya (Indian Journal of Medical and Paediatric Oncology)
Introduction: Carcinoma cervix is the most common gynecological malignancy in India and a major cause of cancer mortality and morbidity in the females despite Concurrent chemoradiotherapy (CCRT). Attempts are on to improved overall survival by addition of adjuvant chemotherapy (ACT) to CCRT. Aim: The aim of this study is to establish toxicity profile of double-agent ACT after CCRT and ICRT in locally advanced cervical cancer (LACC) and to compare it with standard chemoradiation protocol. Materials and Methods: Patients were randomized into two arms: in conventional arm (Arm 1, n = 23), patients received a standard protocol of weekly injection cisplatin 40 mg/m2 concurrently with pelvic external beam radiotherapy (5040cGy/28 fractions) followed by ICRT (03 fractions of 7 Gy each). In interventional arm (Arm 2, n = 24), patients received CCRT/ICRT protocol; and were further offered ACT with three cycles of consolidation chemotherapy using injection paclitaxel and injection carboplatin every 3 weeks after CCRT and ICRT. Results: The incidence of anemia was 14/23 (50% Grade 1) in Arm 1 and 12/24 in Arm 2 (17% Grade 1, rest higher grade). In Arm 2, 37% of patients had ≥Grade 2 neuropathy and 16% of patients had Grade 1 alopecia, whereas nil incidence was reported in Arm 1 (P = 0.005 and 0.04, respectively). Grade 3 neutropenia was observed in 4/23 (17%) patients of Arm 1 and 8/24 patients (33%) of Arm 2. None of the patients in Arm 1 required indoor supportive care while 4/24 patients (17%) were managed as an indoor patient. Among late toxicities, in Arm 2, the incidence of Grade 2 and Grade 3 anemia was 42%, whereas in Arm 1, its incidence was 22%. In Arm 1, no patient exhibited features of neuropathy, whereas, in Arm 2, 12/24 (50%) of the patients had neuropathy (P value for these two late events was <0.05 statistically significant). No therapy-induced mortality was noted. Conclusion: Exhibition of ACT with injection Paclitaxel and injection carboplatin in locally advanced carcinoma cervix is a technically viable option with manageable toxicity.